2017
DOI: 10.1016/j.neuron.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Architecture of AMPA-Type Glutamate Receptors and Their Auxiliary Proteins

Abstract: AMPA receptors (AMPARs) are tetrameric ion channels that together with other ionotropic glutamate receptors (iGluRs), the NMDA and kainate receptors, mediate a majority of excitatory neurotransmission in the central nervous system. Whereas NMDA receptors gate channels with slow kinetics, responsible primarily for generating long-term synaptic potentiation and depression, AMPARs are the main fast transduction elements at synapses and are critical for the expression of plasticity. The kinetic and conductance pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
332
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 322 publications
(338 citation statements)
references
References 208 publications
(313 reference statements)
4
332
1
1
Order By: Relevance
“…CUB domain-containing proteins, including SOL-1 and SOL-2 in C. elegans , and Netos 1 and 2 in mouse associate with glutamate receptors and regulate their channel properties and trafficking (Greger et al, 2016; Howe, 2015; Jackson and Nicoll, 2011; Straub and Tomita, 2012; Vernon and Swanson, 2017; Wang et al, 2012a). Similar to these proteins, the N-terminal portion of the Npn-2 extracellular domain harbors two CUB domains (Pasterkamp, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CUB domain-containing proteins, including SOL-1 and SOL-2 in C. elegans , and Netos 1 and 2 in mouse associate with glutamate receptors and regulate their channel properties and trafficking (Greger et al, 2016; Howe, 2015; Jackson and Nicoll, 2011; Straub and Tomita, 2012; Vernon and Swanson, 2017; Wang et al, 2012a). Similar to these proteins, the N-terminal portion of the Npn-2 extracellular domain harbors two CUB domains (Pasterkamp, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…We found that Npn-2 coimmunoprecipitates most robustly with GluA1, and to a much lesser extent with GluA2 (Figure 5A). Npn-2 does not coimmunoprecipitate with other glutamate receptors, including the kainate receptor subunit GluK2, which interacts with the CUB domain-containing transmembrane proteins Neto1 and Neto2, or the NMDAR subunit NR2A, which interacts with Neto1 (Greger et al, 2016; Howe, 2015; Jackson and Nicoll, 2011; Straub and Tomita, 2012; Vernon and Swanson, 2017; Wang et al, 2012a). (Figures 5A and 5B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations